2014
DOI: 10.1152/jn.00501.2013
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of motion processing through echolocation, source hearing, and vision in blind echolocation experts and sighted echolocation novices

Abstract: Thaler L, Milne JL, Arnott SR, Kish D, Goodale MA. Neural correlates of motion processing through echolocation, source hearing, and vision in blind echolocation experts and sighted echolocation novices. J Neurophysiol 111: 112-127, 2014. First published October 16, 2013 doi:10.1152/jn.00501.2013.-We have shown in previous research (Thaler L, Arnott SR, Goodale MA. PLoS One 6: e20162, 2011) that motion processing through echolocation activates temporal-occipital cortex in blind echolocation experts. Here we in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
66
1
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(72 citation statements)
references
References 41 publications
4
66
1
1
Order By: Relevance
“…Recruiting was an issue because of the time investment in training sighted subjects. Our results are also supported by previous work on the relationship between acoustic features of echolocation vocalizations and performance for object detection (Thaler and Castillo-Serrano, 2016).…”
Section: Room Size Discriminationsupporting
confidence: 90%
See 2 more Smart Citations
“…Recruiting was an issue because of the time investment in training sighted subjects. Our results are also supported by previous work on the relationship between acoustic features of echolocation vocalizations and performance for object detection (Thaler and Castillo-Serrano, 2016).…”
Section: Room Size Discriminationsupporting
confidence: 90%
“…Neuroimaging studies on echolocation have shown that the presentation of spatialized echoes to blind echolocation experts results in strong activations of visual cortical areas (Thaler et al, 2011(Thaler et al, , 2014b. In these studies, participants did not vocalize during imaging, an approach we will refer to as "passive echolocation."…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, we would expect this relationship between VVI and echo ability to generalize to other echolocation tasks, unless performance in the echolocation task did not involve calcarine cortex. In recent work we have shown that processing of echo-motion in blind and sighted people relies on activity in temporal-occipital, rather than calcarine cortex (Thaler et al 2013a). Based on this we would expect that performance in an echolocation task that relies exclusively on processing of echo-motion should not correlate with VVI.…”
Section: Generalization Of Findings To Other Echolocation Tasksmentioning
confidence: 99%
“…Ammons et al 1953;Worchel and Mauney 1951) and that reflected sound waves can provide skilled echolocators with a wealth of useful information about the reflecting object -e.g. position, distance, size, and density (for reviews see for example Schenkman and Nilsson 2010;Stoffregen and Pittenger 1995), as well as motion (Rosenblum et al 2000;Thaler et al 2013a). On a purely physical basis, information about these properties is carried through mono-and binaural variations in echo timing, spectrum (pitch) and intensity (loudness), and people may be able to exploit these variables for echolocation (Cotzin and Dallenbach 1950;Papadopoulos et al 2011;Rosenblum et al 2000;Schenkman and Nilsson 2010;Stoffregen and Pittenger 1995), though the use of one or the other acoustic variable may also depend on the echolocation task people engage in.…”
mentioning
confidence: 99%